Analysing the Financial Governance of Community Forestry in Mid-Hills of Nepal: A Case Study from Tanahu District - Bista, Rajesh; Parajuli, Rajan; Song, Conghe (Journal of Forest and Livelihood, 2024)
In Nepal, community forestry (CF) is a renowned functional community-based institution, contributing to various development interventions at the local level. While numerous studies have focused on conservation aspects of CF, empirical studies on its financial governance are limited. This case study of 246 CFs from Tanahu district in Mid Hills of Nepal analyses the income and expenditure patterns of community forestry user groups (CFUGs) to understand its economic contribution to the local development. A two part model, comprising a logistic regression and a generalised linear model, was used to assess the impacts of significant factors on income level, examining the factors affecting income of the CFUGs. Additionally, the paper also explores the pro-poor programmes priortised by the CFUGs, along with challenges and opportunities of mobilising community forestry funds for local government planning and development in the changing political context.